Peru : First Review Under the Stand-By Arrangement; Staff Report; Staff Statement Press Release on the Executive Board Discussion; and Statement by the Executive Director for Peru. (IMF Staff Country Reports; Country Report ;, 2007)
This paper presents Peru's First Review Under the Stand-By Arrangement for SDR 172.37 million approved on January 26, 2007. Implementing sound macroeconomic policies and reforms would reduce vulnerabilities, entrench sustainable growth, and reduce poverty, setting the stage for a strong exit from IMF-supported programs and for achieving investment grade. The economic outlook remains favorable, with risks largely dependent on external conditions, most notably related to commodity prices and global financial conditions.